IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON ORGANIZATION PERFORMANCE - Dr. VIJAYA LAKSHMI POTHURAJU, Dr. P ALEKHYA (International Journal of Advanced Science and Technology, 2020)
This paper aims to present the organization's performance for socially responsible actions, inInformation Technology (IT) sector to contribute to improving the competitiveness of those organizations.The analysis is from different levels of employees working for the organization. It investigates the linkamong firms ‟relationship with employees with the objective to find out if there is a competitiveadvantage in applying Corporate Social Responsibilities practices. Besides the direct influence ofCorporate Social Responsibility practices on organization performance, quality of work-life has beenanalyzed. The empirical analysis was constructed on survey data through the Chi-square test. Toaccomplish this research objective data were collected from a sample of selected IT companies inHyderabad. Respondents were employees working at different levels in the organizations. The outcomeshows that there is a strong connection between corporate Social responsibility practices andorganization performance. In addition, the significant relationship in developing Social ResponsibilitiesPractices positively translates, with quality of work life.